Proximal and distal middle cerebral artery diameter ratio and lenticulostriate artery infarction. - Jun Sang Yoo; Jae Hyun Choi; Jae Young Park; Jeong Yun Song; Jun Young Chang; Dong-Wha Kang; Sun U Kwon; Hang Jin Jo; Bum Joon Kim (PLoS ONE)
Background Lipohyalinotic degeneration (LD) and branch atheromatous disease (BAD) can contribute to subcortical infarctions in the lenticulostriate artery (LSA) territory. This study aimed to identify the association between the proximal and distal middle cerebral artery (MCA) diameter ratio and the two different pathomechanisms of LSA infarction. Methods Patients with acute LSA infarctions categorized as small vessel occlusive disease were included. Demographic and clinical data, along with MCA geometrical variables, were collected. LD and BAD were differentiated based on the length of the infarction diameter and number of axial slices. The proximal/distal M1 diameter ratio was calculated. MCA geometrics between LD and BAD were compared. Independent factors associated with LD were investigated. Computational fluid dynamics (CFD) analysis was used to evaluate hemodynamic parameters. Results A total of 117 patients were included, of whom 64 (54.7%) and 53 (45.3%) were classified as BAD and LD, respectively. LD was associated with hypertension and favorable prognosis. MCA geometric variables revealed that LD had a higher proximal/distal M1 diameter ratio, indicating a potential distinguishing factor. Multivariate analysis confirmed the independent association between LD and the proximal/distal M1 diameter ratio. The proximal/distal M1 diameter ratio also showed a positive correlation with the number of ipsilesional lacunes. CFD analysis showed that the LD model had faster, greater blood influx into LSAs and higher wall shear stress and pressure gradient compared with the BAD model. Conclusions This study suggests MCA geometry, particularly the proximal/distal M1 diameter ratio, may serve as an independent factor for identifying LD.